Analysis of The Graduates' Requirement of Aviation Vocational Colleges in Indonesia - Supardam, Dhian; Surtiningtyas, Sri Rahayu; Rifai, Moch; Prayitno, Hadi (Langit Biru: Jurnal Ilmiah Aviasi, 2025)
This research examines the importance of Human Resource (HR) competencies in the rapidly growing aviation industry in Indonesia, highlighting the need for improved flight services and operations. HR competencies encompassing knowledge, skills, attitudes and personal values ​​are needed, with a focus on HR management functions vital to operational success. The research found that the market demand for vocational college graduates is high, especially for those with relevant licenses and certifications. Stakeholder satisfaction with the performance and quality of graduates is high, determined by the relevance of the curriculum, quality of training, and field work experience. Minimum expected skill standards include communication skills, critical thinking, leadership, safety awareness and interpersonal skills. Recommendations include aligning the curriculum with industry needs, developing soft skills, and integrating the latest technology in learning to prepare graduates for the challenges of the aviation industry.